Cooperative spectrum sensing algorithm based on limiting eigenvalue distribution - Yin MI; Guang-yue LU (Tongxin xuebao)
A novel maximum-minimum eigenvalue (NMME) cooperative spectrum sensing algorithm and threshold decision rule are proposed via analyzing minimum eigenvalue limiting distribution of the covariance matrix of the received signals from multiple cognitive users (CU) by means of latest random matrix theory (RMT).The proposed scheme could not need the prior knowledge of the signal transmitted from primary user (PU) and could effectively overcome the noise uncertainty.At a given probability of false alarm (Pfa),simulation results show that the proposed scheme can get lower decision threshold and higher probability of detection (Pd) compared with the original algorithm,and it can also get better detection performance with fewer CU and smaller sample numbers.